Ethylene-vinyl acetate copolymer resin, film, molded article, foamed article and sheet

By adjusting the vinyl acetate content and the vinyl acetate content rate, combined with specific antioxidant content and treatment conditions, a large number of ethylene-vinyl acetate copolymer resins with excellent fish eye increase resistance, strength deterioration resistance, yellowing resistance and pollution resistance were prepared, solving the problem of insufficient recycling performance in the prior art.

CN116535556BActive Publication Date: 2025-04-29ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310107868.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-02-02
Filing Date
2023-01-31
Publication Date
2025-04-29
Estimated Expiration
2043-01-31

AI Technical Summary

Technical Problem

When the prior art reuses the ethylene-vinyl acetate copolymer resin, there are shortcomings in fish eye increase resistance, strength deterioration resistance, yellowing resistance and pollution resistance.

Method used

By adjusting the vinyl acetate content and the vinyl acetate content, combined with specific antioxidant content and treatment conditions, a large amount of ethylene-vinyl acetate copolymer resin with excellent fish eye increase resistance, strength deterioration resistance, yellowing resistance and pollution resistance were prepared.

Benefits of technology

The recycling performance of ethylene-vinyl acetate copolymer resin is significantly improved, including fish eye increase resistance, strength deterioration resistance, yellowing resistance and pollution resistance, and the amount of floc is small.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116535556B_ABST
    Figure CN116535556B_ABST
Patent Text Reader

Abstract

The present invention relates to ethylene-vinyl acetate copolymer resins, films, molded articles, foams, and sheets. The present invention provides ethylene-vinyl acetate copolymer resins, films, molded articles, foams, and sheets in which the increase rate of fish-eye resistance, strength deterioration resistance, yellowing resistance, and stain resistance of recycled products of the ethylene-vinyl acetate copolymer resin are excellent and the amount of flocs is small. An ethylene-vinyl acetate copolymer resin, wherein the ethylene-vinyl acetate copolymer resin contains vinyl acetate units, and the ethylene-vinyl acetate copolymer resin satisfies the following conditions (1) and (2): (1) The vinyl acetate content measured according to JIS K7192 is 8% by mass or more and 20% by mass or less. (2) The linked vinyl acetate content ratio determined by <supgt;13< / supgt;C-NMR is 0.05 / 100C or more and 0.38 / 100C or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an ethylene-vinyl acetate copolymer resin, a film, a molded body, a foamed body and a sheet. Background Art

[0002] Ethylene-vinyl acetate copolymer resins are used in a wide range of industrial fields as films, cushioning materials, etc. due to their excellent properties such as flexibility, transparency, heat sealing properties, weather resistance and durability. For example, they are used as special polyolefin films for agriculture, polyolefin packaging materials, stretch films, protective films, melt bags, cushioning materials for vehicle parts, fenders, waterproof sheets for construction and civil engineering, droppers, artificial turf mats for electric wires, road cones, etc.

[0003] In recent years, the requirements for quality have been increasing year by year, and the society is also paying more attention to environmental issues. As a countermeasure to environmental issues, it is expected to develop raw materials with less impact on the environment, Resins and resin recycling technology, etc.

[0004] For example, Patent Document 1 proposes an ethylene-vinyl acetate copolymer resin and a film which are excellent in film forming processability and excellent in appearance when formed into a film.

[0005] In addition, for example, Patent Document 2 states that in order to overcome the brittleness of biomass resins and recycled composite resins, a highly flexible ethylene-vinyl acetate copolymer resin is added to improve impact resistance and elongation at break, thereby helping to reduce the environmental impact of various uses such as films and molded bodies.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent No. 6933755

[0009] Patent Document 2: Japanese Patent Application Publication No. 2021-80428 Summary of the invention

[0010] Problems to be solved by the invention

[0011] However, as shown in Patent Document 1, in order to meet the required high-quality characteristics, ethylene-vinyl acetate copolymer resins and films with excellent film processing properties and excellent appearance when formed into films have been developed. However, there are still problems with the fisheye increase resistance rate during recycling, resistance to strength degradation, yellowing resistance, and stain resistance required to cope with environmental issues.

[0012] In addition, in Patent Document 2, the brittleness of the recycled composite resin is overcome by formulating a plurality of ethylene-vinyl acetate copolymer resins having a high vinyl acetate content concentration and high softness. However, there are problems to be improved in terms of the fisheye increase resistance rate, strength degradation resistance, yellowing resistance and stain resistance when the ethylene-vinyl acetate copolymer resin itself is recycled.

[0013] Here, fisheye refers to a state where the peripheral portion of the film becomes uneven due to the presence of a gel-like substance in the film, and is one of the problems that may occur in a resin film because it looks like fisheye when observed with the naked eye, a polarizing plate or a microscope.

[0014] The present invention has been made in view of the above problems, and an object of the present invention is to provide a recycled product of ethylene-vinyl acetate copolymer resin which has excellent fisheye increase resistance, strength degradation resistance, yellowing resistance and stain resistance and has good flocculent properties in order to improve the recycling performance and high quality. Small amounts of ethylene-vinyl acetate copolymer resins, films, molded bodies, foams and sheets.

[0015] In addition, the inventors used 13 C-NMR was used to analyze the molecular structure of ethylene-vinyl acetate copolymer resin. As a result, it was inferred that the vinyl acetate (chain anhydride) ) signal position, and found that the content of linked vinyl acetate affects the recycling performance of ethylene-vinyl acetate copolymer resin.

[0016] Means used to solve problems

[0017] Therefore, the present inventors have conducted intensive studies to solve the above problems. As a result, it has been found that by having an ethylene-vinyl acetate copolymer resin with a specific vinyl acetate content and a specific linked vinyl acetate content, an ethylene-vinyl acetate copolymer resin having excellent fisheye increase resistance, strength degradation resistance, yellowing resistance and stain resistance and a small amount of flocs in a recycled product of the ethylene-vinyl acetate copolymer resin can be obtained, and the above problems can be solved, thereby completing the present invention.

[0018] That is, the present invention is as follows. [1]

[0020] An ethylene-vinyl acetate copolymer resin, wherein the ethylene-vinyl acetate copolymer resin comprises vinyl acetate units, and the ethylene-vinyl acetate copolymer resin satisfies the following conditions (1) and (2):

[0021] (1) A vinyl acetate content of 8% by mass or more and 20% by mass or less as measured in accordance with JIS K7192;

[0022] (2) By 13 The linked vinyl acetate content determined by C-NMR was 0.05 / 100C or more and 0.38 / 100C or less. [2]

[0024] The ethylene-vinyl acetate copolymer resin according to [1], wherein the melt flow rate of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7210 is 0.5 g / 10 min or more and 20 g / 10 min or less. [3]

[0026] The ethylene-vinyl acetate copolymer resin according to [1] or [2], wherein the content of the antioxidant is 2500 ppm or less based on the total amount of the ethylene-vinyl acetate copolymer resin. [4]

[0028] The ethylene-vinyl acetate copolymer resin according to any one of [1] to [3], wherein the yellowing degree of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7373:2006 after the ethylene-vinyl acetate copolymer resin is exposed to a constant temperature and humidity chamber at a temperature of 40° C. and a humidity of 90% for 30 days is 0.3 or less. [5]

[0030] The ethylene-vinyl acetate copolymer resin according to any one of [1] to [4], wherein the yellowing degree of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7373:2006 after the ethylene-vinyl acetate copolymer resin is exposed to a constant temperature and humidity chamber at a temperature of 40° C. and a humidity of 90% for 30 days is not less than −1.5. [6]

[0032] The ethylene-vinyl acetate copolymer resin as described in any one of [1] to [5], wherein the thermogravimetric loss (Lw) of the ethylene-vinyl acetate copolymer resin after heating the ethylene-vinyl acetate copolymer resin at a temperature of 300° C. in a nitrogen atmosphere using a thermogravimetric measuring device for 6 hours is 20% by weight or less. [7]

[0034] The ethylene-vinyl acetate copolymer resin as described in any one of [1] to [6], wherein the ethylene-vinyl acetate copolymer resin is heated at 300°C with a temperature increase rate of 5°C / min in a nitrogen atmosphere using a thermogravimetric measuring apparatus, and the volatile component thermogravimetric loss (Vc) of the ethylene-vinyl acetate copolymer resin at 300°C is 0.7 wt% or less. [8]

[0036] The ethylene-vinyl acetate copolymer resin according to any one of [1] to [7], wherein the molecular weight distribution (Mw / Mn) of the ethylene-vinyl acetate copolymer resin is 3.0 or more and 7.0 or less. [9]

[0038] A film comprising the ethylene-vinyl acetate copolymer resin according to any one of [1] to [8].

[10]

[0040] The film as described in [9], wherein the film is used for packaging and / or melt bags.

[11]

[0042] The film according to [9] or

[10] , wherein the film has two or more layers.

[12]

[0044] The film according to any one of [9] to

[11] , wherein the film is a stretched film.

[13]

[0046] A molded article comprising the ethylene-vinyl acetate copolymer resin according to any one of [1] to [8].

[14]

[0048] A foam comprising the ethylene-vinyl acetate copolymer resin according to any one of [1] to [8].

[15]

[0050] A sheet comprising the ethylene-vinyl acetate copolymer resin according to any one of [1] to [8].

[0051] Effects of the Invention

[0052] According to the present invention, it is possible to provide an ethylene-vinyl acetate copolymer resin, a film, a molded product, a foamed product and a sheet having excellent fisheye increase resistance, strength degradation resistance, yellowing resistance and stain resistance and a small amount of flocs as a recycled product of the ethylene-vinyl acetate copolymer resin. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 Ethylene-vinyl acetate copolymer resin 13 An example of calculating the linked vinyl acetate content from C-NMR measurement results. DETAILED DESCRIPTION

[0054] Hereinafter, an embodiment of the present invention (hereinafter referred to as “this embodiment”) will be described in detail, but the present invention is not limited thereto and various modifications can be made without departing from the gist of the invention.

[0055] [Ethylene-vinyl acetate copolymer resin]

[0056] The ethylene-vinyl acetate copolymer resin of the present embodiment comprises vinyl acetate units having a vinyl acetate content of 8% by mass or more and 20% by mass or less as measured in accordance with JIS K7192 and ethylene units. 13 The linked vinyl acetate content determined by C-NMR was 0.05 / 100C or more and 0.38 / 100C or less.

[0057] The present inventors have conducted intensive studies and found that, by having a prescribed ratio of vinyl acetate units in the ethylene-vinyl acetate copolymer resin and a linked vinyl acetate content within a certain range, the fisheye increase resistance, strength degradation resistance, yellowing resistance and stain resistance of the recycled product of the ethylene-vinyl acetate copolymer resin of the present embodiment are further improved.

[0058] The reason is not particularly limited, but for example, it is believed that the following reasons are the reason: since the content of linked vinyl acetate is relatively low, the intermolecular binding energy is low, and there are fewer branched structures that are easily thermally decomposed, the probability of thermal degradation during thermal decomposition and cross-linking during recycling is reduced, and the deterioration of resin quality caused by yellowing of the resin during recycling and increase in fish-eye rate is suppressed, thereby improving the recycling performance of the resin.

[0059] On the other hand, it is believed that by increasing the content of linked vinyl acetate to a certain value or more, the entanglement of the molecular chains is enhanced due to the dipole interaction between the carbonyl group and the methyl group between the side chains of the nearby acetoxy groups, thereby making it difficult for the molecular chains to be untangled during processing such as extruders and molding, thereby suppressing the deterioration of mechanical strength and improving the recyclability of the resin.

[0060] In this embodiment, by 13 C-NMR defines the content of linked vinyl acetate contained in the ethylene-vinyl acetate copolymer. 13 C-NMR is a method that places a sample in a strong magnetic field, irradiates molecules with consistent nuclear spin directions with pulsed radio waves to cause nuclear magnetic resonance, and then detects the signal generated when the molecules return to the stable state before excitation to analyze the molecular structure, etc. The molecular structure can be qualitatively and quantitatively analyzed based on the position and area intensity of the object signal in the NMR spectrum.

[0061] Hereinafter, the ethylene-vinyl acetate copolymer resin according to the present embodiment will be described in detail.

[0062] [Link to vinyl acetate content]

[0063] The definition of "linked vinyl acetate content" in the present embodiment will be described in detail below.

[0064] First, we calculated the number of 13 In the case of the displacement value of C, the signal of the unlinked vinyl acetate branch was observed at around 75.3 ppm. When the number is two or more links, due to the shielding effect, the signal is observed at around 72.3 ppm, which is 3 ppm shifted to the high magnetic field side relative to the signal of the unlinked vinyl acetate branch. When the number is three or more links, due to the shielding effect, the signal is observed at around 69.3 ppm, which is 6 ppm shifted to the high magnetic field side relative to the signal of the unlinked vinyl acetate branch.

[0065] like Figure 1 As shown, in fact, in the ethylene-vinyl acetate copolymer resin 13 In the C-NMR measurement results, the signal of the unchained vinyl acetate branch was observed at around 74.4 ppm. When the number of chains is two or more, the signal is shifted to the high magnetic field side by about 3 ppm relative to the signal of the unchained vinyl acetate branch due to the shielding effect, and when the number of chains is three or more, the signal is shifted to the high magnetic field side by about 4 ppm relative to the signal of the unchained vinyl acetate branch due to the shielding effect. The positions of the signals near 71.6 ppm and 70.7 ppm can be attributed to the signals of the chained vinyl acetate. Here, the reason for defining them as "near" is that the positions of the signals are slightly shifted as a whole due to the vinyl acetate content.

[0066] It should be noted that, as 13 The ethylene-vinyl acetate copolymer resin (hereinafter also referred to as a sample) used in C-NMR can be pretreated by weighing the sample, adding o-dichlorobenzene-d4 as a solvent, and shaking at 130°C for 240 minutes to dissolve the sample.

[0067] Based on the above, the definition of the linked vinyl acetate content in the present embodiment will be described below.

[0068] (Link to the definition of vinyl acetate content)

[0069] In this embodiment, the linked vinyl acetate content is defined as follows: AVANCE-500HD manufactured by Bruker Corporation is used as 13 The C-NMR measurement device is set to observe the core 13C, set the observation frequency to 125.77 MHz, the pulse width to 5.0 μs, the PD to 5 s, the measurement temperature to 120°C, the number of integration times to 8000 times, the solvent to o-dichlorobenzene-d4, the sample concentration to 5 weight / volume %, and the dissolution temperature to 130°C, and then Figure 1 As shown, it will be 13 The signal position of the methylene carbon signal of polyethylene observed in the C-NMR spectrum was based on 29.9 ppm, and its area intensity was set to 100. The linked vinyl acetate content was defined by the sum of the ratios of the area intensities near 71.6 ppm and 70.7 ppm.

[0070] Here, whether or not the above “near” is met means that the signal is close to and can include 71.6 ppm and / or 70.7 ppm in its peak width. Specifically, near 71.6 ppm is preferably 71.3 ppm to 71.9 ppm, and near 70.7 ppm is preferably 70.4 ppm to 71.0 ppm.

[0071] The linked vinyl acetate content is 0.05 / 100C or more and 0.38 / 100C or less, preferably 0.05 / 100C or more and 0.35 / 100C or less, and more preferably 0.10 / 100C or more and 0.30 / 100C or less. When the linked vinyl acetate content is 0.05 / 100C or more, the recycled product of the ethylene-vinyl acetate copolymer resin has excellent resistance to strength degradation. In addition, when the linked vinyl acetate content is 0.38 / 100C or less, the recycled product has excellent resistance to yellowing and resistance to fisheye increase rate.

[0072] Here, " / 100C" as a unit of the vinyl acetate content means that, as described above, 13 The ratio of the area intensity when the signal position is based on 29.9 ppm of the methylene carbon signal of polyethylene observed in the C-NMR spectrum and the area intensity is set to 100.

[0073] There are no particular limitations on the method for adjusting the linked vinyl acetate content within the above range, and examples thereof include a method of uniformly dispersing vinyl acetate monomers in ethylene and then polymerizing. There are no particular limitations on the specific method, and for example, by diluting a free radical polymerization initiator with isoparaffin or the like and adding a relatively low concentration of the free radical polymerization initiator for polymerization, local introduction of vinyl acetate units into the polyethylene chain can be suppressed, and relatively uniform polymerization can be performed from the front section to the rear section of the polymerization reactor, and continuous introduction of vinyl acetate can be suppressed, so that the linked vinyl acetate content can be adjusted within the above range.

[0074] In addition, other methods for adjusting the linked vinyl acetate content within the above range are not particularly limited. For example, by continuously changing the opening of a valve in a pipe located upstream of the polymerization reactor and immediately before the polymerization reactor, or by installing a mesh-shaped static mixer in the pipe located upstream of the polymerization reactor and immediately before the polymerization reactor, a part of the laminar flow flowing in the pipe is disturbed, and a turbulent flow is formed to make the laminar flow uniform, thereby making it possible to uniformly disperse the vinyl acetate monomer in ethylene, and thus the linked vinyl acetate content can be adjusted within the above range.

[0075] In addition, there are no particular limitations on other methods for adjusting the linked vinyl acetate content to the above range. For example, in order to match the target vinyl acetate content, the vinyl acetate monomer can be added to ethylene from multiple locations before the polymerization reactor, so that the vinyl acetate monomer can be uniformly dispersed in the ethylene, thereby adjusting the linked vinyl acetate content to the above range.

[0076] [Vinyl acetate content]

[0077] The content of the vinyl acetate unit of the ethylene-vinyl acetate copolymer resin of the present embodiment is 8% by mass or more and 20% by mass or less, preferably 9% by mass or more and 19% by mass or less, and more preferably 10% by mass or more and 18% by mass or less, relative to the total amount of the ethylene-vinyl acetate copolymer resin. When the content of the vinyl acetate unit is 8% by mass or more, the resin has excellent resistance to strength degradation during recycling. In addition, when the content of the vinyl acetate unit is 20% by mass or less, the resin has excellent heat resistance, and thus the recycled product of the ethylene-vinyl acetate copolymer resin has excellent resistance to fisheye increase rate caused by thermal degradation and yellowing.

[0078] The method for adjusting the vinyl acetate content is not particularly limited, and examples thereof include appropriately adjusting the amount of vinyl acetate added in the step of polymerizing the ethylene-vinyl acetate copolymer. It should be noted that the vinyl acetate content can be measured by preparing a calibration curve by saponification and potentiometric titration as a standard test method according to JIS K7192:1999, and converting the vinyl acetate content by infrared spectroscopy as a control test method. More specifically, the content is measured by the method described in the Examples described below.

[0079] [Melt flow rate]

[0080] The melt flow rate of the ethylene-vinyl acetate copolymer resin of the present embodiment is preferably 0.5 g / 10 minutes or more and 20 g / 10 minutes or less, more preferably 1 g / 10 minutes or more and 17 g / 10 minutes or less, and further preferably 2 g / 10 minutes or more and 15 g / 10 minutes or less. When the melt flow rate is 0.5 g / 10 minutes or more, the amount of low molecular weight components that are easily degraded and highly volatile tends to decrease, and the yellowing resistance caused by thermal degradation during recycling and reuse, especially the pollution resistance, is excellent. In addition, when the melt flow rate is 20 g / 10 minutes or less, the resin heat caused by the shearing of the extruder is small, the entanglement of the molecular chain is not easy to untie, and the recycled product of the ethylene-vinyl acetate copolymer resin has excellent resistance to strength degradation.

[0081] There are no particular limitations on the method for adjusting the melt flow rate of the ethylene-vinyl acetate copolymer resin. For example, the method includes adjusting the reaction temperature and / or reaction pressure, the type or amount of the chain transfer agent, etc. when polymerizing the ethylene-vinyl acetate copolymer. More specifically, when polymerizing the ethylene-vinyl acetate copolymer, when the reaction temperature is increased, the melt flow rate of the ethylene-vinyl acetate copolymer resin tends to increase, when the reaction pressure is increased, the melt flow rate of the ethylene-vinyl acetate copolymer resin tends to decrease, and when the amount of the chain transfer agent is increased, the melt flow rate tends to increase. It should be noted that the melt flow rate can be measured according to JIS K7210: 1999 CODE D (temperature = 190°C, load = 2.16 kg). Specifically, it is measured by the method described in the examples described later.

[0082] [Antioxidant]

[0083] The content of the antioxidant in the ethylene-vinyl acetate copolymer resin of the present embodiment is preferably 2500 ppm or less, more preferably 2000 ppm or less, and further preferably 1000 ppm or less relative to the total amount of the ethylene-vinyl acetate copolymer resin. When the content of the antioxidant is 2500 ppm or less, the oozing out of the additive can be suppressed, so that the content of the molded product and the contact object have excellent contamination resistance. In addition, for example, the coloring component of the modified product derived from the antioxidant decreases, and the yellowing resistance of the recycled product of the ethylene-vinyl acetate copolymer resin is excellent.

[0084] In addition, the content of the antioxidant in the ethylene-vinyl acetate copolymer resin of the present embodiment is preferably 300 ppm or more, and more preferably 500 ppm or more, relative to the total amount of the ethylene-vinyl acetate copolymer resin. When the content of the antioxidant is 300 ppm or more, the degradation of the ethylene-vinyl acetate copolymer resin caused by oxygen can be prevented, and the generation of fisheyes during recycling and molding can be suppressed, so the fisheye resistance increase rate of the recycled product is excellent.

[0085] There is no particular limitation on the method for adjusting the content of the antioxidant, and examples thereof include appropriately adjusting the amount of the antioxidant added in the step of polymerizing the ethylene-vinyl acetate copolymer. It should be noted that the content of the antioxidant can be measured by a high performance liquid chromatograph by a standard addition method. Specifically, it can be measured by the method described in the examples described below.

[0086] [Yellowing degree]

[0087] The yellowing degree of the ethylene-vinyl acetate copolymer resin of the present embodiment is preferably -1.5 or more and 0.3 or less, more preferably -1.0 or more and 0.3 or less, and further preferably -0.5 or more and 0 or less. When the yellowing degree is -1.5 or more, the color change is small, so the appearance change of the molded sheet is small, and the recycled product of the ethylene-vinyl acetate copolymer resin is excellent in yellowing resistance. In addition, when the yellowing degree is 0.3 or less, yellowing is small, and the recycled product is more excellent in yellowing resistance.

[0088] The method for adjusting the yellowing degree is not particularly limited, and examples thereof include adjusting the amount of antioxidant added in the step of polymerizing the ethylene-vinyl acetate copolymer, and removing hydroquinone which is usually added as a polymerization inhibitor for the vinyl acetate monomer by distillation before polymerization.

[0089] The yellowing degree can be measured in accordance with JIS K 7373. Specifically, the yellowing degree is measured by the method described in the examples described below.

[0090] [Thermogravimetric loss (Lw)]

[0091] The thermogravimetric loss (Lw) of the ethylene-vinyl acetate copolymer resin of the present embodiment is preferably 20.0% or less, more preferably 17.5% or less, and further preferably 15.0% or less. When the thermogravimetric loss (Lw) is 20.0% or less, the recycled product of the ethylene-vinyl acetate copolymer resin has excellent yellowing resistance and fisheye increase resistance due to thermal degradation.

[0092] The method for adjusting the thermogravimetric loss (Lw) is not particularly limited, and examples thereof include a method of reducing the content of linked vinyl acetate and a method of adding a large amount of an antioxidant.

[0093] The thermogravimetric loss (Lw) can be measured using a thermogravimetric measuring device. Specifically, it can be measured by the method described in the examples described below.

[0094] [Thermogravimetric loss of volatile components (Vc)]

[0095] The volatile component thermogravimetric loss (Vc) of the ethylene-vinyl acetate copolymer resin of the present embodiment is preferably 0.7% or less, more preferably 0.6% or less, and further preferably 0.5% or less. When the volatile component thermogravimetric loss (Vc) is 0.7% or less, the amount of easily volatile components such as low molecular weight components is small, so the viscosity of the pellets is reduced, and the friction in piping transportation can be reduced, so the generation of flocs of the ethylene-vinyl acetate copolymer resin can be suppressed. In addition, the content of the molded product and the contact object are excellent in contamination resistance.

[0096] There are no particular limitations on the method for reducing the thermogravimetric loss (Vc) of volatile components. For example, a method of blowing and removing relatively high temperature dry air for a long time in a silo storing pellets of ethylene-vinyl acetate copolymer resin obtained by polymerization can be cited. In addition, although there are no particular limitations, another method for reducing the thermogravimetric loss (Vc) of volatile components is as follows: when a large amount of solvents such as isoparaffin are added, low molecular weight volatile components increase, and therefore a relatively high concentration of a free radical polymerization initiator is added to carry out polymerization.

[0097] The volatile component thermogravimetric loss (Vc) can be measured using a thermogravimetric measuring device. Specifically, it can be measured by the method described in the examples described below.

[0098] [Molecular weight distribution (Mw / Mn)]

[0099] The molecular weight distribution (Mw / Mn) of the ethylene-vinyl acetate copolymer of the present embodiment is preferably 3.0 or more and 7.0 or less, and more preferably 4.0 or more and 6.0 or less. When the molecular weight distribution (Mw / Mn) is 3.0 or more, the heat generation of the resin caused by high viscosity during extrusion under high shear can be suppressed, so the entanglement of the molecular chain is not easy to untie, and the recycled product of the ethylene-vinyl acetate copolymer resin has excellent resistance to strength degradation. In addition, when the molecular weight distribution (Mw / Mn) is 7.0 or less, there is a tendency that the amount of low molecular weight components that are easily degraded is small, and the recycled product of the ethylene-vinyl acetate copolymer resin has excellent resistance to yellowing caused by thermal degradation.

[0100] The method for adjusting the molecular weight distribution (Mw / Mn) is not particularly limited, and the molecular weight distribution can be adjusted by adjusting the polymerization temperature, the polymerization pressure, and the like.

[0101] The molecular weight distribution (Mw / Mn) is measured by gel permeation chromatography (hereinafter also referred to as "GPC") and can be obtained based on a calibration curve prepared using commercially available monodisperse polystyrene. Specifically, the molecular weight distribution (Mw / Mn) is measured by the method described in the examples described below.

[0102] [Ethylene unit]

[0103] The content of ethylene units in the ethylene-vinyl acetate copolymer resin of the present embodiment is preferably greater than 80% by mass and less than 92% by mass, more preferably greater than 81% by mass and less than 91% by mass, and further preferably greater than 82% by mass and less than 90% by mass, relative to the total amount of the ethylene-vinyl acetate copolymer resin. When the content of ethylene units is greater than 80% by mass, the heat resistance is excellent, and thus the yellowing resistance and fisheye increase rate caused by thermal degradation during recycling are excellent. In addition, when the content of ethylene units is less than 92% by mass, the recycled product of the ethylene-vinyl acetate copolymer resin is excellent in resistance to strength degradation.

[0104] The ethylene-vinyl acetate copolymer resin of the present embodiment may contain monomer units other than the ethylene unit and the vinyl acetate unit. There are no particular limitations on the other monomer units, and examples thereof include units of propylene and butane.

[0105] The ethylene-vinyl acetate copolymer resin of the present embodiment can be a resin obtained by dry-blending or melt-blending two or more ethylene-vinyl acetate copolymer resins at an arbitrary ratio. When two or more ethylene-vinyl acetate copolymer resins are used, it is preferred that the content of vinyl acetate units in the entire resins is within the above range.

[0106] [Method for producing ethylene-vinyl acetate copolymer resin]

[0107] The ethylene-vinyl acetate copolymer resin of the present embodiment is not particularly limited, and can be obtained, for example, by polymerizing ethylene and vinyl acetate monomers under pressure and heating in the presence of a polymerization initiator. A chain transfer agent may be added to the polymerization system as needed.

[0108] The polymerization reactor of ethylene-vinyl acetate copolymer is not particularly limited, and examples thereof include autoclaves and tubular reactors. Among them, a tubular reactor is preferably used. By using a plug-flow tubular reactor, since back mixing does not occur, the introduction of vinyl acetate into the growing polymer chain can be suppressed, and the content of linked vinyl acetate can be easily and appropriately adjusted.

[0109] There are no particular limitations on the polymerization initiator, and examples thereof include free radical initiators such as peroxides, etc. There are no particular limitations on the free radical initiators such as peroxides, and examples thereof include tert-butyl peroxy(2-ethylhexanoate), tert-butyl peroxyacetate, tert-butyl peroxypivalate, di-tert-butyl peroxide, etc.

[0110] There is no particular limitation on the dilution of the polymerization initiator added to the reactor, and an isoparaffin solvent or the like can be used. The concentration of the diluted polymerization initiator is preferably 1 wt % to 13 wt %, more preferably 4 wt % to 10 wt %, and even more preferably 5 wt % to 8 wt %. By adding the diluted polymerization initiator, the linked vinyl acetate content can be easily adjusted to the above range.

[0111] The isoparaffin solvent is not particularly limited, but is preferably a solvent having 10 to 15 carbon atoms, and specific examples thereof include isodecane, isoundecane, and isododecane.

[0112] The vinyl acetate monomer may be added after the polymerization inhibitor such as hydroquinone contained in the vinyl acetate monomer is removed by distillation. By using the vinyl acetate monomer after removing the polymerization inhibitor of the vinyl acetate monomer, the yellowing degree can be easily adjusted to the above range.

[0113] In addition, in order to match the target vinyl acetate content, when adding vinyl acetate monomer to ethylene before the polymerization reactor, it can be added from multiple locations. The vinyl acetate monomer is preferably added from 2 to 3 locations, more preferably 3 locations. By adding vinyl acetate monomer from multiple locations, it is easy to adjust the linked vinyl acetate content to the above range.

[0114] There are no particular restrictions on the chain transfer agent, and examples thereof include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, and isobutanol; alkanes or alkenes such as ethane, propane, propylene, butane, 1-butene, and 2-butene; and ketones or aldehydes such as acetone, methyl ethyl ketone, 2-pentanone, 3-pentanone, 2-hexanone, 3-hexanone, diisobutyl ketone, methyl isopropyl ketone, formaldehyde, acetaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde, and isovaleraldehyde.

[0115] The ethylene and vinyl acetate monomers supplied to the reactor may be in a gaseous state or in a liquid state.

[0116] When ethylene or the like to which vinyl acetate monomer is added is introduced into the polymerization reactor, a mesh-shaped static mixer may be provided in the piping immediately before the polymerization reactor and on the upstream side of the polymerization reactor. By providing a static mixer in the piping immediately before the polymerization reactor and on the upstream side of the polymerization reactor, it is easy to adjust the linked vinyl acetate content within the above range.

[0117] In addition, when ethylene or the like to which vinyl acetate monomer is added is introduced into the polymerization reactor, the opening of the valve of the pipe connected to the upstream side of the polymerization reactor can be continuously changed. By continuously changing the opening of the valve of the pipe connected to the upstream side of the polymerization reactor, the bound vinyl acetate content can be easily adjusted to the above range.

[0118] The average polymerization temperature is preferably 150° C. to 280° C., more preferably 180° C. to 260° C. In addition, the polymerization pressure is preferably 100 MPa to 350 MPa, more preferably 120 MPa to 270 MPa, and further preferably 180 MPa to 260 MPa. It should be noted that the “average polymerization temperature” herein refers to the average value of the temperature at each position from the most upstream to the most downstream in the polymerization reactor.

[0119] The polymerization reactor may have a plurality of sites for supplying raw materials such as ethylene, vinyl acetate monomer, and polymerization initiator.

[0120] The ethylene-vinyl acetate copolymer obtained by the polymerization as described above is subjected to pressure reduction in a high-pressure separator and a low-pressure separator to separate unreacted raw materials and the like from the ethylene-vinyl acetate copolymer resin.

[0121] The ethylene-vinyl acetate copolymer resin whose linked vinyl acetate content is adjusted to the above range has a small number of branched structures that are easily thermally decomposed, and the probability of thermal degradation is reduced, so the container temperature of the low-pressure separator can be increased. The container temperature of the low-pressure separator is preferably 180°C to 240°C, and more preferably 240°C. By setting the container temperature of the low-pressure separator to a relatively high temperature of 180°C to 240°C and maintaining a low resin viscosity, the retention of the molten resin in the low-pressure separator can be suppressed, and the thermal degradation of the ethylene-vinyl acetate copolymer resin can be suppressed.

[0122] In the high-pressure separator and the low-pressure separator, the molten ethylene-vinyl acetate copolymer resin and the unreacted gases such as the raw material ethylene gas and vinyl acetate gas exist in the form of a gas-liquid mixed fluid. The unreacted gas can be recovered from the upper part of the container of each separator, sent to the inlet of the multi-stage compressor, and reused in the polymerization.

[0123] The ethylene-vinyl acetate copolymer resin separated as described above is preferably pelletized by an extruder, and then dry air at 20° C. to 80° C. is blown into a silo storing the pellets for 9 hours or more. From the viewpoint of removing low molecular weight volatile components, the temperature of the dry air is preferably 50° C. to 70° C., more preferably 60° C. to 70° C.

[0124] The time for blowing dry air is preferably 18 hours or longer, more preferably 24 hours or longer.

[0125] [additive]

[0126] The ethylene-vinyl acetate copolymer resin of the present embodiment may contain additives such as a slip agent, an antioxidant, a light resistance stabilizer, an anti-blocking agent, and an antistatic agent as necessary.

[0127] The lubricant is not particularly limited, and examples thereof include aliphatic hydrocarbons, fatty acid esters of alcohols, waxes, higher fatty acid amides, silicone oils, and rosin.

[0128] The antioxidant is not particularly limited, and examples thereof include phenolic antioxidants such as 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; phosphorus-containing antioxidants such as tris(2,4-di-tert-butylphenyl) phosphite and tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphite; phosphorus-containing / phenolic antioxidants such as 6-tert-butyl-4-[3-(2,4,8,10-tetra-tert-butyldibenzo[d,f]][1,3,2]dioxaphosphin-6-yloxy)propyl]-o-cresol; and sulfur-containing antioxidants such as dilauryl thiodipropionate.

[0129] The content of the antioxidant in the ethylene-vinyl acetate copolymer resin is not particularly limited, but is preferably 2500 ppm or less, more preferably 2000 ppm or less, and further preferably 1000 ppm or less. In addition, the content of the antioxidant in the ethylene-vinyl acetate copolymer resin is more preferably 300 ppm or more, and further preferably 500 ppm or more.

[0130] The light stabilizer is not particularly limited, and specific examples include benzotriazole-based light stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; and hindered amine-based light stabilizers such as bis(2,2,6,6-tetramethyl-4-piperidinyl)sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}]

[0131] The anti-blocking agent is not particularly limited, and examples thereof include aluminosilicate, kaolin, natural silica, synthetic silica, talc, and diatomaceous earth.

[0132] The antistatic agent is not particularly limited, and examples thereof include nonionic surfactants, ionic surfactants, amphoteric surfactants, and mixtures thereof.

[0133] [Molding body]

[0134] The molded body of the present embodiment comprises the above-mentioned ethylene-vinyl acetate copolymer resin. The molded body of the present embodiment is not particularly limited, and can be obtained, for example, by injection molding, extrusion molding, and stretch molding, and can be applied to various uses. Specifically, there is no particular limitation, and examples thereof include: electronic equipment, cushioning materials for vehicle-mounted components, road cones, artificial turf mats, automobile fenders, fender covers, drainage hoses, etc. In addition, it can also be used as fibers, etc.

[0135] [Sheet]

[0136] The sheet of the present embodiment comprises the above-mentioned ethylene-vinyl acetate copolymer resin. The sheet can be produced by, for example, T-die molding, inflation molding, calendar molding, slice molding, etc. T-die or extrusion molding, inflation molding are particularly preferred.

[0137] The sheet material of this embodiment can be appropriately used for automobile fenders and fender covers. It should be noted that "sheet material" refers to a plastic thin plate-like article with a thickness of 250 μm or more. The thickness of the sheet material of this embodiment is preferably 250 μm or more, more preferably 300 μm to 10 mm, and further preferably 0.5 mm to 10 mm.

[0138] [Foam]

[0139] The foam of this embodiment includes the ethylene-vinyl acetate copolymer resin. The foam of this embodiment can be obtained using foamed fine particles and the like, and is not particularly limited in its use, and can be suitably used in various applications such as cushioning materials for electronic devices and vehicle-mounted parts.

[0140] [membrane]

[0141] The film of the present embodiment comprises the above-mentioned ethylene-vinyl acetate copolymer resin. As the manufacturing method of the film, it can be appropriately selected according to the purpose, without particular limitation, and for example, T-die molding, inflation molding, calendering molding, slice molding, etc. can be cited. Inflation molding or T-die extrusion molding are particularly preferred.

[0142] The film of the present embodiment can be appropriately used for agricultural polyolefin-based special films, packaging films, melt bag films, polyolefin packaging materials, stretch films, and flexible container outer packaging films, and more preferably agricultural polyolefin-based special films, polyolefin packaging materials, and packaging and / or stretch films. Specifically, there is no particular limitation, and examples thereof include: stretch films, food packaging films, food cling films, packaging films, shrinkable packaging films, sealing films, etc. Here, stretch films refer to films used when articles are wrapped or packaged.

[0143] It should be noted that the term "film" refers to a plastic film having a thickness of less than 250 μm. The thickness of the film of the present embodiment is preferably 10 μm to 240 μm, and more preferably 10 μm to 200 μm.

[0144] In addition, the film of the present embodiment may have two or more layers, and may have a laminated structure having other layers in addition to the layer containing the ethylene-vinyl acetate copolymer resin. There are no particular restrictions on the method for manufacturing such a laminated film, and for example, a method for manufacturing by laminating or a method for manufacturing by a laminating extrusion process may be cited.

[0145] Example

[0146] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples. The present invention is not limited to the following Examples.

[0147] First, the measurement methods used in each of the Examples and Comparative Examples are described in detail below.

[0148] <Measurement method>

[0149] [Determination of vinyl acetate unit content]

[0150] According to JIS K7192:1999, as a standard test method, a calibration curve was prepared using a VAC reference sample of an ethylene-vinyl acetate copolymer resin having a known vinyl acetate unit content by saponification and potentiometric titration, and as a control test method, the vinyl acetate unit content (VA content) in the ethylene-vinyl acetate copolymer resins obtained in Examples and Comparative Examples was measured by infrared spectroscopy.

[0151] [ 13 C-NMR measurement (linked vinyl acetate content)]

[0152] As a sample pretreatment, the sample was weighed, and a solvent of o-dichlorobenzene-d4 was added, followed by shaking at 130° C. for 240 minutes to dissolve the sample. 13 The C-NMR measurement was performed under the following measurement conditions.

[0153] (Measurement conditions)

[0154] Measurement device: AVANCE-500HD manufactured by Bruker

[0155] Observation core: 13 C

[0156] Observation frequency: 125.77MHz

[0157] Pulse width: 5.0 microseconds

[0158] PD: 5 seconds

[0159] Measuring temperature: 120℃

[0160] Cumulative times: 8000 times

[0161] Baseline: 29.9ppm as PE(-eee-) signal

[0162] Solvent: o-dichlorobenzene-d4

[0163] Sample concentration: 5 weight / volume %

[0164] Dissolving temperature: 130℃

[0165] exist Figure 1 In, as 13 A specific example of C-NMR spectrum is shown in Example 8 described later. 13 C-NMR spectrum, such as Figure 1 As shown, the measured under the above conditions 13 The signal of methylene carbon at 29.9 ppm observed in the C-NMR spectrum was used as a reference for the signal position and its area intensity was set to 100. The sum of the ratios of the area intensities of the signals of linked vinyl acetate near 71.6 ppm and near 70.7 ppm was calculated as the linked vinyl acetate content.

[0166] [Determination of Molecular Weight and Molecular Weight Distribution]

[0167] The weight average molecular weight (Mw) and number average molecular weight (Mn) of ethylene-vinyl acetate copolymer resin were determined by gel permeation chromatography (GPC). The ratio (Mw / Mn) of the weight average molecular weight (Mw) and number average molecular weight (Mn) determined by GPC was used as the molecular weight distribution. The molecular weight was calibrated at 12 points in the range of MW (molecular weight) of 1050 to 20600000 of standard polystyrene manufactured by Tosoh Corporation. The MW of each standard polystyrene was multiplied by a coefficient of 0.43 as the polyethylene-converted molecular weight. A calibration straight line was made from the curve of elution time and polyethylene-converted molecular weight to determine the weight average molecular weight (Mw) and number average molecular weight (Mn). The GPC measurement was carried out under the measurement conditions shown below.

[0168] (Measurement conditions)

[0169] Apparatus: GPC-IR manufactured by PolymerChar

[0170] Detector: IR5 manufactured by PolymerChar

[0171] Column: UT-807 (1 piece) manufactured by Showa Denko Co., Ltd. and GMHHR-H(S)HT (2 pieces) manufactured by Tosoh Co., Ltd. connected in series

[0172] Mobile phase: o-dichlorobenzene

[0173] Column temperature: 140°C

[0174] Flow rate: 1.0mL / min

[0175] Sample concentration: 16mg / 8mL

[0176] Sample dissolution temperature: 140°C

[0177] Sample dissolution time: 60 minutes

[0178] [Melt flow rate (MFR) measurement]

[0179] The MFR of the ethylene-vinyl acetate copolymer resin is measured in accordance with JIS K7210: 1999 CODE D (temperature = 190°C, load = 2.16 kg).

[0180] [High Performance Liquid Chromatography (Quantitative and Qualitative Analysis of Liquid Antioxidants)]

[0181] The pellet or molded product sample was hot-pressed at 150°C to a thickness of 1 mm, and then cut into 1 mm squares. About 5 g of the sample and 20 mL of acetone were weighed and placed in a container. The additive was extracted in a shaking constant temperature bath at 60°C for 5 hours. The acetone extract solution was replaced with tetrahydrofuran and then filtered through a syringe filter (pore size 0.2 μm, material PTFE, effective filtration area 1.3 cm 2 The undissolved components were removed through a filter (diameter φ13 mm) and injected into a high performance liquid chromatograph (HPLC), and the additives were measured under the following measurement conditions.

[0182] (Measurement conditions)

[0183] Centralized control device for liquid chromatograph: SCL-10Avp

[0184] Fraction collector (distillation device): FRC-10A

[0185] Liquid delivery unit: LC-10ATvp

[0186] Column oven device: CTO-10Avp

[0187] Detector (UV): SPD-10Avp (set to 280nm)

[0188] Column: STR ODS-Ⅱ manufactured by SHINWA Chemical Industries LTD (stationary phase C18, particle size 5 μm, inner diameter 4.6 mm, length 150 mm)

[0189] Column temperature: 40°C

[0190] Pump flow rate: 1mL / min

[0191] Mobile phase: acetonitrile:tetrahydrofuran = 1:1 mixed solution

[0192] Injection volume: 10 μL

[0193] Using the retention time and peak area measured under the above conditions, the qualitative and quantitative analysis of the additives was performed by the standard addition method.

[0194] [Determination of yellowing degree]

[0195] One cup of pellets was placed in a colorless spiral tube bottle (capacity 110 mL, opening inner diameter φ20.3 mm, cylinder diameter φ40 mm, total length 120 mm), and left to stand for 30 days in the exposure environment shown below without a cover.

[0196] (Exposure environment)

[0197] Device: Constant temperature and humidity KCL-2000A manufactured by EYELA

[0198] Temperature: 40℃

[0199] Humidity: 90%

[0200] The yellowing degree of the initial pellets before entering the exposure environment and the pellets taken out from the exposure environment was measured in accordance with JIS K7373: 2006. The measurement was carried out under the following conditions.

[0201] (Measurement conditions)

[0202] Device: SE6000 manufactured by Nippon Denshoku Industries

[0203] The shape of the test sample: granular

[0204] Sample container: Quartz glass (cylindrical with inner diameter φ30mm and height 30mm)

[0205] Light source used: D65 / 2

[0206] Measurement method: Reflection method

[0207] The yellowing degree was calculated according to the following formula.

[0208] Yellowness=YI-YI0

[0209] YI: Yellowness after exposure

[0210] YI0: Initial yellowness before exposure

[0211] [Measurement of thermogravimetric loss (Lw) using a thermogravimetric measuring device]

[0212] One pellet was pressed to 1 ton using a Pixie tablet molding micro-hydraulic press, and then about 10 mg was placed in an aluminum pan, and the thermogravimetric loss (Lw) of the ethylene-vinyl acetate copolymer resin was measured using a thermogravimetric measuring device under a nitrogen atmosphere. The thermogravimetric analysis was performed under the following measurement conditions.

[0213] (Measurement conditions)

[0214] Apparatus: TGA5500 manufactured by TA Instruments

[0215] Nitrogen volume: sample purge 25mL / min, balance purge 10mL / min

[0216] Operation step 1: Jump to 30.00℃

[0217] Operation step 2: Isothermal for 1.0 minute

[0218] Operation step 3: Jump to 300.00℃

[0219] Operation step 4: Isothermal for 360.0 minutes

[0220] Thermogravimetric loss (Lw) was calculated according to the following formula.

[0221] Lw=(L0-L 360 ) / L0×100

[0222] L0: Sample weight before measurement (mg)

[0223] L 360 : Sample weight after measurement (mg)

[0224] [Measurement of the thermogravimetric loss of volatile components (Vc) using a thermogravimetric measuring device]

[0225] One pellet was pressed by a Pixie tabletting micro-hydraulic press, and then about 10 mg was placed in an aluminum pan, and the volatile component thermogravimetric loss (Vc) of the ethylene-vinyl acetate copolymer resin was measured by a thermogravimetric measuring device under a nitrogen atmosphere. The thermogravimetric analysis was performed under the following measurement conditions.

[0226] (Measurement conditions)

[0227] Apparatus: TGA5500 manufactured by TA Instruments

[0228] Nitrogen volume: sample purge 25mL / min, balance purge 10mL / min

[0229] Operation step 1: Jump to 30.00℃

[0230] Operation step 2: Isothermal for 3.0 minutes

[0231] Operation step 3: Ramp at 5.00°C / min Heating to 300.00℃

[0232] The volatile component thermogravimetric loss (Vc) was calculated according to the following formula.

[0233] Vc=(V0-V 300 ) / V0×100

[0234] V0: Sample weight before measurement (mg)

[0235] V 300 : Sample weight after measurement (mg)

[0236] Next, the evaluation method of each Example and each Comparative Example is described in detail below.

[0237] <Evaluation Method>

[0238] [Amount of flocculent matter]

[0239] 1 kg of pellets of ethylene-vinyl acetate copolymer resin were randomly taken out and sieved through a flat-top metal net (mesh size 9.5 mm) to separate pellets and ribbon-like flocs. The mass of the separated ribbon-like flocs was measured and the mass was taken as the floc amount.

[0240] The evaluation criteria are as follows: ○ and △ represent pass, and × represents fail.

[0241] (Evaluation criteria for the amount of floccules)

[0242] ○: The amount of flocs is 0.5 g or less.

[0243] △: The amount of flocs is greater than 0.5 g and less than 1 g.

[0244] ×: The amount of floccules is 1 g or more.

[0245] [Film production (reference film)]

[0246] Using a T-die film-making machine (HM 40N manufactured by Hokushin Sangyo Co., Ltd., screw diameter 40 mm, die width 300 mm, 80-mesh plain metal screen), ethylene-vinyl acetate copolymer resin was molded under the conditions of barrel temperature 210°C, die temperature 210°C, extrusion rate 5 kg / hour, and thickness 50 μm to obtain a film.

[0247] [Production of recycled membranes (recycled products)]

[0248] Using a single screw extruder SZW50-28VG (screw diameter 50 mm, L / D = 28, no mesh) manufactured by Technovel, ethylene-vinyl acetate copolymer resin was melt-kneaded at a temperature of 200°C and an output of 5 kg / hour to form pellets. Assuming that the material is recycled, the melt-kneading operation was repeated a total of 4 times, and then a T-die film-making machine (HM40N manufactured by Hokushin Sangyo Co., Ltd., screw diameter 40 mm, die width 300 mm, 80 mesh plain metal mesh) was used to form a film at a barrel temperature of 210°C, a die temperature of 210°C, an extrusion rate of 5 kg / hour, and a thickness of 50 μm.

[0249] [Increase in fisheye resistance of recycled products]

[0250] When the above-mentioned reference film and the film of the recycled product were formed, a fisheye counter manufactured by FUTEC Co., Ltd. (detection capability horizontally: 0.04 mm / bit, detection capability vertically: 0.015 mm / scan, light projection distance: 200 mm, light receiving distance: 440 mm, inspection width: 50 mm) installed on the tractor was used for the film of the T-die head, and the inspection area was 5m 2 , the number of FE with a FE size of 0.2 mm or more is counted. The FE increase rate of the recycled product is calculated using the following formula.

[0251] FE increase rate of recycled products = (FE5-FE1) / FE1×100

[0252] FE1: Number of FEs of the reference film [pcs / 5m 2 ]

[0253] FE5: FE quantity of recycled products [pcs / 5m 2 ]

[0254] The evaluation criteria are as follows: ○ and △ represent pass, and × represents fail.

[0255] (Evaluation criteria for fisheye resistance increase rate of recycled products)

[0256] ○: The FE increase rate of the recycled product is 100% or less.

[0257] △: The FE increase rate of the recycled product is greater than 100% and less than or equal to 200%.

[0258] ×: The FE increase rate of the recycled product is greater than 200%.

[0259] [Resistance to strength degradation of recycled products]

[0260] The thickness of the reference film and the film of the recycled product was measured using a constant pressure thickness gauge (manufactured by TECLOCK, model PG-02, minimum display 0.001 mm), and only the portion of the film with a thickness of 50 μm or less ±1% was selected to prepare a test piece of test piece type 5 according to JIS K7127. The tensile test was measured according to JIS K7127 under the following conditions.

[0261] (Measurement conditions)

[0262] Device: TENSIRON (RTC-1310A) manufactured by Orientec

[0263] Pulling speed: 500mm / min

[0264] Measurement temperature: 25℃

[0265] Chuck distance: 80mm

[0266] Direction of test piece: MD (film flow direction)

[0267] The strength degradation of the recycled product is calculated using the following formula.

[0268] Strength degradation of recycled product = (tensile strain 5 - tensile strain 1) / tensile strain 1 × 100

[0269] Tensile strain 1: Tensile strain of reference film [%]

[0270] Tensile strain 5: Tensile strain of recycled product [%]

[0271] The evaluation criteria are as follows: ○ and △ represent pass, and × represents fail.

[0272] (Evaluation criteria for resistance to strength degradation of recycled products)

[0273] ○: The strength of the recycled product deteriorates by -10% or more.

[0274] △: The strength of the recycled product deteriorates by -20% or more and less than -10%.

[0275] ×: The strength deterioration of the recycled product is less than -20%.

[0276] [Yellowing resistance of recycled products]

[0277] A 1m long portion was cut from the film of the above-mentioned regenerated product and left to stand for 30 days in an exposure environment of a thermostatic hygrostat KCL-2000A manufactured by EYELA Co., Ltd. at a temperature of 40°C and a humidity of 90%. The film of the regenerated product taken out and left to stand in the exposure environment was compared with the reference film by visual observation. If no yellowing was observed at all, it was evaluated as excellent in yellowing resistance. On the other hand, if yellowing was clearly observed, it was evaluated as poor in yellowing resistance. In addition, in the middle of the two, if it was uncertain whether yellowing occurred, it was evaluated as slightly better in yellowing resistance.

[0278] The evaluation criteria are as follows: ○ and △ represent pass, and × represents fail.

[0279] (Evaluation criteria for yellowing resistance of recycled products)

[0280] ○: Excellent yellowing resistance.

[0281] △: Slightly better yellowing resistance.

[0282] ×: Poor yellowing resistance.

[0283] [Stain resistance of recycled products]

[0284] When the film of the above-mentioned recycled product is formed, the film of the T-die head is brought into contact with the black felt cloth installed on the guide roller of the traction machine for 300 meters, so that the powder of the film sample is gathered on the felt cloth. The amount and aggregation state of the gathered powder are visually observed. When no powder is generated or a small amount of powder is generated but the aggregation is localized, the pollution resistance is evaluated as excellent. On the other hand, when a large amount of powder is generated and the powder is continuously aggregated in a band at the part where the felt cloth begins to contact, the pollution resistance is evaluated as poor. If the amount and aggregation state of the powder are between the two, the pollution resistance is evaluated as slightly better.

[0285] The evaluation criteria are as follows: ○ and △ represent pass, and × represents fail.

[0286] (Evaluation criteria for contamination resistance of recycled products)

[0287] ○: Excellent stain resistance.

[0288] △: Slightly better stain resistance.

[0289] ×: Poor stain resistance.

[0290] The comprehensive evaluation is as follows, ◎ and ○ represent pass, and × represents fail.

[0291] (Comprehensive evaluation criteria)

[0292] ◎: The evaluation criteria of the amount of floccules, the fisheye increase rate of the recycled product, the strength degradation resistance of the recycled product, and the yellowing resistance of the recycled product were all 0.

[0293] ○: Each evaluation criterion of the amount of floccules, the fisheye increase rate of the recycled product, the strength degradation resistance of the recycled product, and the yellowing resistance of the recycled product was 0 or △.

[0294] ×: At least one of the evaluation criteria of the amount of floccules, the fisheye increase rate of the recycled product, the strength degradation resistance of the recycled product, and the yellowing resistance of the recycled product was ×.

[0295] Next, the preparation methods of each example and each comparative example are described in detail below.

[0296] [Example 1]

[0297] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 228° C. and a polymerization pressure of 216 MPa. The raw material was a raw material in which propylene was fed in a manner of 0.3 mol % relative to ethylene, and vinyl acetate after hydroquinone was removed was fed in a manner of 7 mol % relative to ethylene from three locations. A polymerization initiator was added at three locations of the tubular reactor, and the maximum temperature of the downstream side of each location where the polymerization initiator was added was 255° C., 260° C., and 275° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxy (2-ethylhexanoate) with isoparaffin to 5 wt %. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 180° C. The separated ethylene-vinyl acetate copolymer resin was made into pellets by an extruder, and then 70° C. dry air was blown into the silo storing the pellets for 24 hours to obtain ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the above-mentioned methods. The measurement results are shown in Table 1.

[0298] [Example 2]

[0299] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 235° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which vinyl acetate after hydroquinone was removed was fed from four locations in a manner of 7 mol% relative to ethylene. A polymerization initiator was added at three locations in the tubular reactor, and the maximum temperature values ​​at the downstream side of each location where the polymerization initiator was added were 243° C., 255° C., and 275° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 1% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 240° C. Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant to the separated ethylene-vinyl acetate copolymer resin, and pellets were prepared by an extruder. Then, dry air at 60° C. was blown into the silo storing the pellets for 18 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 1.

[0300] [Example 3]

[0301] The raw material was introduced into the tubular reactor using a mesh static mixer, and polymerization was carried out under the conditions of an average polymerization temperature of 235° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which vinyl acetate after hydroquinone was removed was fed from one place in a manner of 7 mol% relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum temperature of the downstream side of each place where the polymerization initiator was added was 243° C., 255° C., and 275° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 10% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in the high-pressure separator and the low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 180° C. To the separated ethylene-vinyl acetate copolymer resin, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate as an antioxidant was added and pelletized using an extruder. Then, dry air at 70° C. was blown into the silo storing the pellets for 24 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 1.

[0302] [Example 4]

[0303] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 229° C. and a polymerization pressure of 265 MPa. The raw materials were propylene fed in a manner of 0.5 mol% relative to ethylene and vinyl acetate after hydroquinone was removed was fed from three places in a manner of 4 mol% relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum temperature of the downstream side of each place where the polymerization initiator was added was 250° C., 260° C., and 275° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 1% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 240° C. To the separated ethylene-vinyl acetate copolymer resin, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate as an antioxidant was added and pelletized using an extruder. Then, dry air at 70° C. was blown into the silo storing the pellets for 24 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 1.

[0304] [Example 5]

[0305] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 226° C. and a polymerization pressure of 240 MPa. The raw material was a raw material in which propylene was fed in a manner of 1.5 mol % relative to ethylene and vinyl acetate after hydroquinone was removed was fed from two places in a manner of 4 mol % relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum temperature of the downstream side of each place where the polymerization initiator was added was 224° C., 226° C., and 225° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxy (2-ethylhexanoate) with isoparaffin to 10% by weight was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 180° C. The separated ethylene-vinyl acetate copolymer resin was made into pellets by an extruder, and then 60° C. dry air was blown into the silo storing the pellets for 18 hours to obtain ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the above-mentioned methods. The measurement results are shown in Table 1.

[0306] [Example 6]

[0307] While continuously changing the valve opening, raw materials were introduced into the tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 229° C. and a polymerization pressure of 265 MPa. The raw materials were propylene fed at 0.5 mol% relative to ethylene and vinyl acetate fed from three locations at 4 mol% relative to ethylene. A polymerization initiator was added at three locations of the tubular reactor, and the maximum values ​​of the downstream side temperature at each location where the polymerization initiator was added were 245° C., 258° C., and 280° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 10% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in the high-pressure separator and the low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 240° C. To the separated ethylene-vinyl acetate copolymer resin, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate as an antioxidant was added and pelletized using an extruder. Then, dry air at 40° C. was blown into the silo storing the pellets for 9 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 1.

[0308] [Example 7]

[0309] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 229° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which vinyl acetate after hydroquinone was removed was fed from three locations in a manner of 5 mol% relative to ethylene. A polymerization initiator was added at three locations of the tubular reactor, and the maximum temperature values ​​of the downstream side of each location where the polymerization initiator was added were 245° C., 258° C., and 280° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 5% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 240° C. The separated ethylene-vinyl acetate copolymer resin was made into pellets by an extruder, and then 70° C. dry air was blown into the silo storing the pellets for 24 hours to obtain ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the above-mentioned methods. The measurement results are shown in Table 1.

[0310] [Example 8]

[0311] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 215° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which vinyl acetate after hydroquinone was removed was fed from three locations in an amount of 8 mol% relative to ethylene. A polymerization initiator was added at three locations in the tubular reactor, and the maximum temperature of the downstream side of each location where the polymerization initiator was added was 210° C., 220° C., and 225° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 5% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 180° C. Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant to the separated ethylene-vinyl acetate copolymer resin, and pellets were formed by an extruder. Then, dry air at 70° C. was blown into the silo storing the pellets for 24 hours to obtain ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 1.

[0312] [Comparative Example 1]

[0313] The raw materials were introduced into a tubular reactor and polymerized at an average polymerization temperature of 228° C. and a polymerization pressure of 216 MPa. The raw materials were propylene fed at 0.2 mol% relative to ethylene and vinyl acetate after hydroquinone removal was fed from one place at 7 mol% relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum values ​​of the downstream side temperature at each place where the polymerization initiator was added were 255° C., 260° C., and 275° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxy (2-ethylhexanoate) with isoparaffin to 15% by weight was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 130° C. The separated ethylene-vinyl acetate copolymer resin was made into pellets by an extruder, and then 40° C. dry air was blown into the silo storing the pellets for 9 hours to obtain ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods shown above. The measurement results are shown in Table 2.

[0314] [Comparative Example 2]

[0315] The raw materials were introduced into a tubular reactor and polymerized at an average polymerization temperature of 226° C. and a polymerization pressure of 237 MPa. The raw materials were propylene fed at 0.8 mol% relative to ethylene and vinyl acetate after hydroquinone removal was fed from one place at 4 mol% relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum temperature of the downstream side of each place where the polymerization initiator was added was 224° C., 226° C., and 225° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 15% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 130° C. To the separated ethylene-vinyl acetate copolymer resin, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate as an antioxidant was added and pelletized using an extruder. Then, dry air at 40° C. was blown into the silo storing the pellets for 9 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 2.

[0316] [Comparative Example 3]

[0317] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 229° C. and a polymerization pressure of 265 MPa. The raw materials were propylene fed in a manner of 0.5 mol% relative to ethylene, and vinyl acetate after hydroquinone was removed was fed from 5 places in a manner of 4 mol% relative to ethylene. A polymerization initiator was added at 3 places in the tubular reactor, and the maximum temperature of the downstream side of each place where the polymerization initiator was added was 250° C., 260° C., and 275° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 1% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 240° C. To the separated ethylene-vinyl acetate copolymer resin, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate as an antioxidant was added and pelletized using an extruder. Then, dry air at 70° C. was blown into the silo storing the pellets for 24 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 2.

[0318] [Comparative Example 4]

[0319] The raw material was introduced into a tubular reactor and polymerized at an average polymerization temperature of 229° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which vinyl acetate was fed from one place in a manner of 5 mol% relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum values ​​of the downstream side temperature at each place where the polymerization initiator was added were 245° C., 258° C., and 280° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 15% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 130° C. To the separated ethylene-vinyl acetate copolymer resin, octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate as an antioxidant was added and pelletized using an extruder. Then, dry air at 40° C. was blown into the silo storing the pellets for 9 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 2.

[0320] [Comparative Example 5]

[0321] The raw material was introduced into a tubular reactor and polymerized at an average polymerization temperature of 215° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which vinyl acetate after hydroquinone was removed was fed from one place in an amount of 8 mol% relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum temperature of the downstream side of each place where the polymerization initiator was added was 210° C., 220° C., and 225° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 15% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 130° C. Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant to the separated ethylene-vinyl acetate copolymer resin, and pellets were formed by an extruder. Then, dry air at 40° C. was blown into the silo storing the pellets for 9 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 2.

[0322] [Comparative Example 6]

[0323] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 229° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which propylene was fed in a manner of 0.1 mol% relative to ethylene and vinyl acetate after hydroquinone was removed was fed from three places in a manner of 2 mol% relative to ethylene. A polymerization initiator was added at three places in the tubular reactor, and the maximum temperature of the downstream side of each place where the polymerization initiator was added was 244° C., 250° C., and 280° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 5% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 240° C. The separated ethylene-vinyl acetate copolymer resin was made into pellets by an extruder, and then 40° C. dry air was blown into the silo storing the pellets for 9 hours to obtain ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the methods shown above. The measurement results are shown in Table 2.

[0324] [Comparative Example 7]

[0325] A net-shaped static mixer was used, and while the valve opening was continuously changed, a raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 215° C. and a polymerization pressure of 265 MPa. The raw material was a raw material in which vinyl acetate after hydroquinone was removed was fed from 5 locations in a manner of 9 mol% relative to ethylene. A polymerization initiator was added at 3 locations in the tubular reactor, and the maximum temperature values ​​at the downstream side of each location where the polymerization initiator was added were 215° C., 218° C., and 220° C. from the upstream side. As a polymerization initiator, a solution obtained by diluting tert-butyl peroxide (2-ethylhexanoate) and di-tert-butyl peroxide to 5% by weight with isoparaffin was used. The ethylene-vinyl acetate copolymer after polymerization was separated into unreacted raw materials and the like and ethylene-vinyl acetate copolymer resin while reducing the pressure in a high-pressure separator and a low-pressure separator. At this time, the container temperature of the low-pressure separator was set to 180° C. Pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant to the separated ethylene-vinyl acetate copolymer resin, and pellets were formed by an extruder. Then, dry air at 70° C. was blown into the silo storing the pellets for 24 hours to obtain an ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin were measured by the method shown above. The measurement results are shown in Table 2.

[0326] [Comparative Example 8]

[0327] The raw material was introduced into a tubular reactor, and polymerization was carried out under the conditions of an average polymerization temperature of 220° C. and a polymerization pressure of 265 MPa. The raw material was fed from three locations so that vinyl acetate was 5 mol% relative to ethylene. A polymerization initiator was added at three locations in the tubular reactor, and the maximum temperature values ​​at the downstream side of each location where the polymerization initiator was added were 253° C., 249° C., and 290° C. from the upstream side. As the polymerization initiator, a solution obtained by diluting tert-butyl peroxy(2-ethylhexanoate) and di-tert-butyl peroxide to 15% by weight with isoparaffin was used.

[0328] The opening of the valve of the pipe located between the most downstream of the tubular reactor and the high-pressure separator is continuously changed. The polymerized ethylene-vinyl acetate copolymer is separated into unreacted raw materials and ethylene-vinyl acetate copolymer resin while reducing the pressure in the high-pressure separator and the low-pressure separator. At this time, the container temperature of the low-pressure separator is set to 130°C. The separated ethylene-vinyl acetate copolymer resin is made into pellets using an extruder, and then dry air at 40°C is blown into the silo storing the pellets for 9 hours to obtain ethylene-vinyl acetate copolymer resin. The physical properties and characteristics of the obtained ethylene-vinyl acetate copolymer resin are measured by the method shown above. The measurement results are shown in Table 2.

[0329]

[0330]

[0331] Industrial Applicability

[0332] The ethylene-vinyl acetate copolymer of the present invention has industrial applicability as a resin raw material used in a wide range of industrial fields.

Claims

1. An ethylene-vinyl acetate copolymer resin, wherein The ethylene-vinyl acetate copolymer resin comprises vinyl acetate units, and the ethylene-vinyl acetate copolymer resin satisfies the following conditions (1) and (2): (1) A vinyl acetate content of 8% by mass or more and 20% by mass or less as measured in accordance with JIS K7192; (2) By 13 The linked vinyl acetate content determined by C-NMR is 0.05 / 100C or more and 0.38 / 100C or less. The linked vinyl acetate content is defined as follows: Will pass 13 The signal of methylene carbon of polyethylene observed in the C-NMR spectrum at 29.9 ppm was used as a reference for the signal position, its area intensity was set to 100, and the sum of the ratios of the area intensities of 71.3 ppm to 71.9 ppm and 70.4 ppm to 71.0 ppm was defined as the linked vinyl acetate content.

2. The ethylene-vinyl acetate copolymer resin according to claim 1, wherein The linked vinyl acetate content is greater than or equal to 0.05 / 100C and less than or equal to 0.35 / 100C.

3. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The linked vinyl acetate content is greater than or equal to 0.10 / 100C and less than or equal to 0.30 / 100C.

4. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The vinyl acetate content is 9 mass % or more and 19 mass % or less.

5. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The vinyl acetate content is 10% by mass or more and 18% by mass or less.

6. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The melt flow rate of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7210 is 0.5 g / 10 minutes or more and 20 g / 10 minutes or less.

7. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The melt flow rate of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7210 is 1 g / 10 minutes or more and 17 g / 10 minutes or less.

8. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The melt flow rate of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7210 is 2 g / 10 minutes or more and 15 g / 10 minutes or less.

9. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The content of the antioxidant is 2500 ppm or less based on the total amount of the ethylene-vinyl acetate copolymer resin.

10. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The content of the antioxidant is 2000 ppm or less based on the total amount of the ethylene-vinyl acetate copolymer resin.

11. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The content of the antioxidant is 1000 ppm or less based on the total amount of the ethylene-vinyl acetate copolymer resin.

12. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The content of the antioxidant is 300 ppm or more based on the total amount of the ethylene-vinyl acetate copolymer resin.

13. The ethylene-vinyl acetate copolymer resin according to claim 1 or 2, wherein The content of the antioxidant is 500 ppm or more based on the total amount of the ethylene-vinyl acetate copolymer resin.

14. The ethylene-vinyl acetate copolymer resin according to claim 9, wherein The antioxidant is at least one selected from the group consisting of phenolic antioxidants, phosphorus-containing antioxidants, phosphorus-containing / phenolic antioxidants and sulfur-containing antioxidants.

15. The ethylene-vinyl acetate copolymer resin according to claim 14, wherein The phenolic antioxidant is one or more selected from the group consisting of 2,6-di-tert-butyl-4-methylphenol, pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate.

16. The ethylene-vinyl acetate copolymer resin according to claim 14, wherein The phosphorus-containing antioxidant is at least one selected from the group consisting of tris(2,4-di-tert-butylphenyl) phosphite and tetrakis(2,4-di-tert-butylphenyl)-4,4′-biphenylene diphosphite.

17. The ethylene-vinyl acetate copolymer resin according to claim 14, wherein The phosphorus-containing / phenolic antioxidant is 6-tert-butyl-4-[3-(2,4,8,10-tetra-tert-butyldibenzo[d,f]][1,3,2]dioxaphosphin-6-yloxy)propyl]-o-cresol.

18. The ethylene-vinyl acetate copolymer resin according to claim 14, wherein The sulfur-containing antioxidant is dilauryl thiodipropionate.

19. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein After the ethylene-vinyl acetate copolymer resin is exposed in a thermostatic chamber at a temperature of 40° C. and a humidity of 90% for 30 days, the yellowing degree of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7373:2006 is 0.3 or less.

20. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein After the ethylene-vinyl acetate copolymer resin is exposed to a thermostatic chamber at a temperature of 40° C. and a humidity of 90% for 30 days, the yellowing degree of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7373:2006 is 0 or less.

21. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein After the ethylene-vinyl acetate copolymer resin is exposed to a thermostatic chamber at a temperature of 40° C. and a humidity of 90% for 30 days, the yellowing degree of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7373:2006 is not less than −1.

5.

22. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein After the ethylene-vinyl acetate copolymer resin is exposed in a thermostatic chamber at a temperature of 40° C. and a humidity of 90% for 30 days, the yellowing degree of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7373:2006 is not less than −1.

0.

23. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein After the ethylene-vinyl acetate copolymer resin is exposed to a thermostatic chamber at a temperature of 40° C. and a humidity of 90% for 30 days, the yellowing degree of the ethylene-vinyl acetate copolymer resin measured in accordance with JIS K7373:2006 is not less than −0.

5.

24. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein When the ethylene-vinyl acetate copolymer resin is heated at 300° C. in a nitrogen atmosphere using a thermogravimetric measuring apparatus for 6 hours, the thermogravimetric loss (Lw) of the ethylene-vinyl acetate copolymer resin is 20% by weight or less.

25. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein When the ethylene-vinyl acetate copolymer resin is heated at 300° C. in a nitrogen atmosphere using a thermogravimetric measuring apparatus for 6 hours, the thermogravimetric loss (Lw) of the ethylene-vinyl acetate copolymer resin is 17.5% by weight or less.

26. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein When the ethylene-vinyl acetate copolymer resin is heated at 300° C. in a nitrogen atmosphere using a thermogravimetric measuring apparatus for 6 hours, the thermogravimetric loss (Lw) of the ethylene-vinyl acetate copolymer resin is 15.0% by weight or less.

27. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The ethylene-vinyl acetate copolymer resin is heated at a starting point of 30° C. and a heating rate of 5° C. / min in a nitrogen atmosphere using a thermogravimetric measuring apparatus, and the thermogravimetric loss (Vc) of volatile components at 300° C. of the ethylene-vinyl acetate copolymer resin is 0.7 wt % or less.

28. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The ethylene-vinyl acetate copolymer resin is heated at a starting point of 30° C. and a heating rate of 5° C. / min in a nitrogen atmosphere using a thermogravimetric measuring apparatus, and the volatile component thermogravimetric loss (Vc) of the ethylene-vinyl acetate copolymer resin at 300° C. is 0.6 wt % or less.

29. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The ethylene-vinyl acetate copolymer resin is heated at a starting point of 30° C. and a heating rate of 5° C. / min in a nitrogen atmosphere using a thermogravimetric measuring apparatus, and the thermogravimetric loss (Vc) of volatile components at 300° C. of the ethylene-vinyl acetate copolymer resin is 0.5 wt % or less.

30. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The molecular weight distribution (Mw / Mn) of the ethylene-vinyl acetate copolymer resin is 3.0 or more and 7.0 or less.

31. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The molecular weight distribution (Mw / Mn) of the ethylene-vinyl acetate copolymer resin is 4.0 or more and 6.0 or less.

32. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The content of ethylene units in the ethylene-vinyl acetate copolymer resin is greater than 80% by mass and less than 92% by mass based on the total amount of the ethylene-vinyl acetate copolymer resin.

33. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The content of the ethylene units in the ethylene-vinyl acetate copolymer resin is more than 81% by mass and less than 91% by mass with respect to the total amount of the ethylene-vinyl acetate copolymer resin.

34. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The content of ethylene units in the ethylene-vinyl acetate copolymer resin is more than 82% by mass and less than 90% by mass relative to the total amount of the ethylene-vinyl acetate copolymer resin.

35. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The ethylene-vinyl acetate copolymer resin further contains monomer units other than the ethylene unit and the vinyl acetate unit.

36. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, wherein The ethylene-vinyl acetate copolymer resin further contains additives.

37. The ethylene-vinyl acetate copolymer resin according to claim 36, wherein The additive is at least one selected from the group consisting of a slip agent, a light stabilizer, an anti-blocking agent, and an antistatic agent.

38. The ethylene-vinyl acetate copolymer resin according to claim 37, wherein The lubricant is at least one selected from the group consisting of aliphatic hydrocarbons, fatty acid esters of alcohols, waxes, higher fatty amides, silicone oils, and rosins.

39. The ethylene-vinyl acetate copolymer resin according to claim 37, wherein The light stabilizer is at least one selected from the group consisting of benzotriazole-based light stabilizers and hindered amine-based light stabilizers.

40. The ethylene-vinyl acetate copolymer resin according to claim 39, wherein The benzotriazole-based light stabilizer is at least one selected from the group consisting of 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole.

41. The ethylene-vinyl acetate copolymer resin according to claim 39, wherein The hindered amine light stabilizer is one or more selected from the group consisting of bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate, poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidinyl)imino}].

42. The ethylene-vinyl acetate copolymer resin of claim 37, wherein The anti-blocking agent is at least one selected from the group consisting of aluminosilicate, kaolin, natural silica, synthetic silica, talc, and diatomaceous earth.

43. The ethylene-vinyl acetate copolymer resin of claim 37, wherein The antistatic agent is at least one selected from the group consisting of a nonionic surfactant, an ionic surfactant, an amphoteric surfactant, and a mixture thereof.

44. The ethylene-vinyl acetate copolymer resin according to any one of claims 1, 2, 14 to 18, and 37 to 43, wherein The ethylene-vinyl acetate copolymer resin has a flocculent amount of more than 0.5 g and less than 1 g, or less than 0.5 g.

45. A method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 1 to 44, wherein: The ethylene-vinyl acetate copolymer resin is obtained by polymerizing ethylene and vinyl acetate monomers under pressure and heating in the presence of a polymerization initiator.

46. ​​A method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 1 to 44, wherein: The ethylene-vinyl acetate copolymer resin is obtained by polymerizing ethylene and vinyl acetate monomers under pressure and heating in the presence of a polymerization initiator and a chain transfer agent.

47. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 46, wherein The chain transfer agent is one or more selected from the group consisting of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, ethane, propane, propylene, butane, 1-butene, 2-butene, acetone, methyl ethyl ketone, 2-pentanone, 3-pentanone, 2-hexanone, 3-hexanone, diisobutyl ketone, methyl isopropyl ketone, formaldehyde, acetaldehyde, n-butyraldehyde, isobutyraldehyde, n-valeraldehyde and isovaleraldehyde.

48. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47, wherein The polymerization reactor of the ethylene-vinyl acetate copolymer resin is an autoclave or a tubular reactor.

49. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 48, wherein The polymerization reactor of the ethylene-vinyl acetate copolymer resin is a plug-flow tubular reactor.

50. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 48, wherein A static mixer is provided in the pipe located upstream of the polymerization reactor and immediately before the polymerization reactor.

51. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 50, wherein: The opening degree of the valve of the pipe connected to the polymerization reactor on the upstream side thereof was continuously changed.

52. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 50, wherein: A mesh-shaped static mixer is installed in the pipe on the upstream side of the polymerization reactor and immediately before the polymerization reactor to turbulent a part of the laminar flow flowing in the pipe.

53. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 48, wherein When vinyl acetate monomer is added to ethylene before the polymerization reactor, it is added from multiple locations.

54. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The average polymerization temperature is 150°C or higher and 280°C or lower.

55. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The average polymerization temperature is 180°C or higher and 260°C or lower.

56. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The polymerization pressure is 100 MPa or more and 350 MPa or less.

57. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The polymerization pressure is 120 MPa or more and 270 MPa or less.

58. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The polymerization pressure is 180 MPa or more and 260 MPa or less.

59. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein While the pressure is reduced in the high-pressure separator and the low-pressure separator, the unreacted raw material is separated from the ethylene-vinyl acetate copolymer resin.

60. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 59, wherein The container temperature of the low-pressure separator is 180° C. or higher and 240° C. or lower.

61. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The polymerization initiator is a free radical polymerization initiator.

62. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 61, wherein The radical polymerization initiator is one or more peroxide radical initiators selected from the group consisting of tert-butyl peroxy(2-ethylhexanoate), tert-butyl peroxyacetate, tert-butyl peroxypivalate, and di-tert-butyl peroxide.

63. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The polymerization initiator is diluted with an isoparaffin solvent.

64. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 63, wherein The isoparaffin solvent is a solvent having 10 or more and 15 or less atoms.

65. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 64, wherein The isoparaffin solvent is at least one selected from the group consisting of isodecane, isoundecane, and isododecane.

66. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The vinyl acetate monomer is used after removing its inhibitor.

67. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The concentration of the polymerization initiator is 1 wt % or more and 13 wt % or less.

68. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The concentration of the polymerization initiator is 4 wt % or more and 10 wt % or less.

69. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The concentration of the polymerization initiator is 5 wt % or more and 8 wt % or less.

70. The method for producing an ethylene-vinyl acetate copolymer resin according to any one of claims 45 to 47 and 50 to 53, wherein The ethylene-vinyl acetate copolymer resin is made into pellets by an extruder, and then dry air at a temperature of 20° C. to 80° C. is blown into a silo storing the pellets for more than 9 hours.

71. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 70, wherein: The temperature of the dry air is 50° C. or higher and 70° C. or lower.

72. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 70, wherein: The temperature of the dry air is 60° C. or higher and 70° C. or lower.

73. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 70, wherein: The time for spraying dry air is more than 18 hours.

74. The method for producing an ethylene-vinyl acetate copolymer resin according to claim 70, wherein: The time for spraying dry air is more than 24 hours.

75. A membrane, wherein The film comprises the ethylene-vinyl acetate copolymer resin according to any one of claims 1 to 44.

76. The film of claim 75, wherein The films are used for packaging and / or melt bags.

77. The membrane of claim 75 or 76, wherein The film has two or more layers.

78. The membrane of claim 75 or 76, wherein The film is a stretched film.

79. The membrane of claim 75 or 76, wherein The film is used for agricultural polyolefin special films, packaging films, melt bag films, polyolefin packaging materials, and stretch films.

80. The membrane of claim 75 or 76, wherein The film is used as a film for outer packaging of flexible containers.

81. The film of claim 75 or 76, wherein The thickness of the film is less than 250 μm.

82. The membrane of claim 75 or 76, wherein The film has a thickness of 10 μm to 240 μm.

83. The membrane of claim 75 or 76, wherein The thickness of the film is 10 μm to 200 μm.

84. The membrane of claim 75 or 76, wherein The FE increase rate of the regenerated product of the membrane is greater than 100% and less than or equal to 200%.

85. The membrane of claim 75 or 76, wherein The FE increase rate of the regenerated product of the membrane is less than 100%.

86. The membrane of claim 75 or 76, wherein The strength degradation of the regenerated product of the membrane is greater than or equal to -20% and less than -10%.

87. The membrane of claim 75 or 76, wherein The strength of the regenerated product of the membrane deteriorates by more than -10%.

88. A method for producing a film according to any one of claims 75 to 87, wherein: The film is produced by any one of T-die molding, inflation molding, calendaring molding and slice molding.

89. A molded body, wherein The molded article comprises the ethylene-vinyl acetate copolymer resin according to any one of claims 1 to 44.

90. The molded article according to claim 89, wherein The molded body is used for electronic equipment, cushioning materials of vehicle-mounted components, road cones, artificial turf mats, automobile fenders, fender covers, drainage hoses or fibers.

91. A method for producing a molded article according to claim 89 or 90, wherein: The molded body is manufactured by injection molding, extrusion molding or stretching molding.

92. A foam, wherein: The foam comprises the ethylene-vinyl acetate copolymer resin according to any one of claims 1 to 44.

93. The foam according to claim 92, wherein The foam is used as a cushioning material for electronic equipment and vehicle-mounted components.

94. A sheet material, wherein The sheet comprises the ethylene-vinyl acetate copolymer resin according to any one of claims 1 to 44.

95. The sheet material of claim 94, wherein The sheet is used for automobile fenders and fender covers.

96. The sheet material of claim 94 or 95, wherein: The sheet has a thickness of 250 μm or more.

97. The sheet material of claim 94 or 95, wherein: The thickness of the sheet is 300 μm to 10 mm.

98. The sheet material of claim 94 or 95, wherein: The thickness of the sheet is 0.5 mm to 10 mm.

99. A method for producing a sheet according to any one of claims 94 to 98, wherein: The sheet is manufactured by T-die molding, inflation molding, calendering molding or slice molding.

Citation Information

Patent Citations

  • Resin composition and molding using the resin composition

    JP2021080428A

  • Manufacturing Method Of Ethylene-vinyl Acetate Copolymer Resin Used For Solar Cell Sealing Sheet And Resin Manufactured Thereby

    CN106916241A

  • KR20210010375A